Double-Take : A Revisionist Harlem Renaissance Anthology - Honey, Maureen, 1945-; Patton, Venetria K., 1968- (Book collections on Project MUSE., 2001)
Brings together a comprehensive selection of texts from the Harlem Renaissance-a key period in the literary and cultural history of the United States. Offers a unique, balanced collection of writers--men and women, gay and straight, familiar and obscure. Arranged by author, rather than by genre, this anthology includes works from major Harlem Renaissance figures as well as often-overlooked essayists, poets, dramatists, and artists. Contains works from a wide variety of genres--poetry, short stories, drama, and essays, as well as biographical sketches of the authors. Includes most pieces in their entirety. Also includes artwork and illustrations, many of which are from original journals and have never before been reprinted, and song lyrics to illustrate the interrelation of various art forms.